Implementasi Sensory Immersion dan Interactive Agent Control Pada Sistem Pemasaran Perumahan Melalui Teknologi Virtual Reality - Rizal Darmawansyah; Wibisono Sukmo Wardhono; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Globally, the marketing method of a property product is still using conventional method. But there are other factors that can be used to attract buyers' attention through the buyer's psychological side. Some of the elements that can be used are through immersive and interactive agent control. The immersive element is used to stimulate the buyer's senses which in this case the spatial audio is used as the medium. For the element of interactive agent control is used as a buyer interaction with the product that will be a virtual agent and those elements will be implemented on virtual reality technology. To determine the performance of each functional, the system will be tested through black-box testing, and usability scale testing in the form of usability score and likert scale to determine the quality of the system in qualitative and quantitative. The results of the black-box testing obtained function of the system has been running well with some scenarios that exist with 100% success rate. From the tests that have been done, the system got 64,5 for usability scale score that categorized in C class and obtained the system can be mastered easily, work consistently and well. But on the comfort side, there are some users that feel dizzy cause the perform of the system has not optimal.